The Relationship Between Parenting Patterns and Toilet Training Skills in Pre-School Children at Paud Kober Al-Husa Tambak Kibin Serang - Oktaviani, Rizky (Journal of Smart Nursing and Health Science, 2024)
Background: Indonesia in 2017 is known that the number of children under five in 2016 amounted to 30%, out of 258,704,986 people in Indonesia there are 75 million people who fall into the category of pre-school age children. namely, children who experience conditions unable to control urination and defecation independently. This condition occurs because parents are unable to toilet train their children, therefore this happens because children do not understand the concept of toilet training which should be done independently. Indonesia also has 50% (52,226) cases of bedwetting problems that occur in children. Purpose: This study aims to determine the relationship between parenting patterns and toilet training skills in preschool children.Methods: This type of research is correlative analytic research with Cross-Sectional design. The research sample using purposive sampling obtained a sample of 47 respondents. The research instruments used were the parenting questionnaire and the toilet training ability questionnaire. Univariate data were analyzed descriptively and bivariate data were analyzed using the Chi-Square test. Results: the results of the Chi-Square test obtained a P-Value of 0.01 is smaller than the significant value (a=0.05).Conclusion: The results showed that there is a relationship between parenting patterns and toilet training skills of preschool children